2007
DOI: 10.1093/ps/86.9.1856
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment of Broiler Chickens Given Mushroom Extract Alone or in Combination with Probiotics

Abstract: A study was conducted to evaluate the effect of combined Shiitake mushroom (Lentinus edodes) extract with probiotics (PrimaLac) on the growth and health of broiler chickens. In trial 1, 540 d-of-hatch chicks were randomly assigned to 6 treatment groups, replicated 3 times, with 15 males and 15 females per pen for 3 wk. Dietary probiotics and mushroom treatments were as follows: 1) control feed + ad libitum tap water; 2) control feed + skip-a-day mushroom water; 3) control feed + ad libitum mushroom water; 4) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
54
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(72 citation statements)
references
References 13 publications
12
54
6
Order By: Relevance
“…Also, in results described by Rowghani et al (2007), a combination of probiotic and commercial feed additives had the most positive effect on performance in broilers. These results contrast with the result that broilers fed on either probiotics or mushroom extract were more likely to gain weight than those fed a mixture of them (Willis et al, 2007). Such conflicting results might depend on the type of substances mixed with probiotics.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Also, in results described by Rowghani et al (2007), a combination of probiotic and commercial feed additives had the most positive effect on performance in broilers. These results contrast with the result that broilers fed on either probiotics or mushroom extract were more likely to gain weight than those fed a mixture of them (Willis et al, 2007). Such conflicting results might depend on the type of substances mixed with probiotics.…”
Section: Discussioncontrasting
confidence: 59%
“…Probiotics are a live microbial feed additive that beneficially affects the host animal by improving its intestinal bacterial balance (Fuller, 1989). Chickens fed dietary probiotics showed improved body weight gain (Torres-Rodriguez et al, 2005), reduced mortality (Vicente et al, 2007) and enhanced feed conversion, ultimately resulting in an increase of broiler production (Willis et al, 2007). Also, in this study, the SPB group showed a 2% higher body weight gain than the control.…”
Section: Discussionsupporting
confidence: 54%
“…Also, study of Toghyani et al (2011) indicated that carcass yield and relative organ weights were not influenced by dietary probiotic and prebiotic. In contrast, the study of Willis et al (2007) showed that fat pad relative weights percentage for males and females was affected by treatments and it was lower in birds fed probiotic diet with mushroom extract water in comparison with control diet. Some other factors such as bird species, sex, age, environmental condition, and quantity of added probiotic could affect the effects of probiotics supplementation.…”
Section: Resultsmentioning
confidence: 80%
“…Mortality rate was 4% in all treatments and was not affected by dietary treatments (P>0.05). Similarly, Harrington et al (2014), Kehlet et al (2014), and Willis et al (2007) reported that mortality was not affected by the broiler probiotic diet or mushroom extract water additive.…”
Section: Resultsmentioning
confidence: 91%
“…Chen et al (2013) suggested measuring immune organ weight as a method for evaluating immune status in chickens. Willis et al (2007) also suggested that the bursa was the primary lymphoid organ in broiler chickens and concluded that probiotics could increase the relative weight of bursa to BW. The colour of broiler chicken meat is important because consumers regard it as a sign of a fresh and high quality product.…”
Section: Discussionmentioning
confidence: 99%